Physical Activity, Exercise Testing and Clinical Assessment in Sports Medicine - Rodríguez-Sanz, David (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Physical activity and exercise testing are two key points in sports medicine. Sports medicine is a field of medicine concerned with the prevention and treatment of injuries and disorders that are related to participation in sports. Clinical assessment in sports medicine can solve many questions about diagnosis, treatment, and prognosis related to health in sports. Physical activity could be defined as any bodily movement produced by skeletal muscles that requires energy expenditure. Physical activity refers to all movement including during leisure time, for transport to get to and from places, or as part of a person's work. Both moderate- and vigorous-intensity physical activity improve health. Regular physical activity is proven to help prevent and manage noncommunicable diseases such as heart disease, stroke, diabetes, and several cancers. It also helps prevent hypertension, maintain a healthy body weight, and can improve mental health, quality of life, and well-being. Exercise could be defined as a subset of physical activity that is planned, structured, and repetitive and has as a final or an intermediate objective, such as the improvement or maintenance of physical fitness. Gait and posture analysis, clinical assessment, biomechanical analysis, reliability and repeatability research, force platform and electromyography analysis are key in order to improve our knowledge in this area.